Major Effect of Oxidative Stress on the Male, but Not Female, SP-A1 Type II Cell miRNome - Noutsios, George T.; Thorenoor, Nithyananda; Zhang, Xuesheng; Phelps, David S.; Umstead, Todd M.; Durrani, Faryal; Floros, Joanna (Frontiers in Immunology, 2019)
Pulmonary surfactant protein A (SP-A) plays an important role in surfactant metabolism and lung innate immunity. In humans there are two proteins, SP-A1 and SP-A2, encoded by SFTPA1 and SFTPA2, respectively, which are produced by the alveolar type II cells (T2C). We sought to investigate the differential influence of SP-A1 and SP-A2 in T2C miRNome under oxidative stress (OxS). SP-A knock out (KO) and hTG male and female mice expressing SP-A1 or SP-A2 as well as gonadectomized (Gx) mice were exposed to O3-induced oxidative stress (OxS) or filtered air (FA). Expression of miRNAs and mRNAs was measured in the T2C of experimental animals. (a) In SP-A1 males after normalizing to KO males, significant changes were observed in the miRNome in terms of sex-OxS effects, with 24 miRNAs being differentially expressed under OxS. (b) The mRNA targets of the dysregulated miRNAs included Ago2, Ddx20, Plcg2, Irs1, Elf2, Jak2, Map2k4, Bcl2, Ccnd1, and Vhl. We validated the expression levels of these transcripts, and observed that the mRNA levels of all of these targets were unaffected in SP-A1 T2C but six of these were significantly upregulated in the KO (except Bcl2 that was downregulated). (c) Gondadectomy had a major effect on the expression of miRNAs and in three of the mRNA targets (Irs1, Bcl2, and Vhl). Ccnd1 was upregulated in KO regardless of Gx. (d) The targets of the significantly changed miRNAs are involved in several pathways including MAPK signaling pathway, cell cycle, anti-apoptosis, and other. In conclusion, in response to OxS, SP-A1 and male hormones appear to have a major effect in the T2C miRNome.